2020
DOI: 10.1007/s00167-020-06249-1
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic knotless repair: an effective technique for small-sized supraspinatus tendon tears

Abstract: PurposeThe purpose was to evaluate the clinical and radiological results of knotless repair with flat‐braided suture in full small‐sized supraspinatus tendon tears (< 1 cm). MethodsA consecutive series of 54 patients with isolated small supraspinatus tendon tear (< 1 cm and Goutallier index < 2) was evaluated in the study. Patients underwent a knotless arthroscopic repair using flat‐braided suture (2 mm wide). Minimal follow‐up required was 5 years. Changes in Murley–Constant score, ASES score, strength, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Predicting a retear before surgery may help surgeons and patients select the optimal treatment. Regarding the retear rate, many previous studies have reported retear rates ranging from 5 to 57% [1, 6, 7, 9, 12, 13, 16, 20, 22–24, 26, 31, 32, 34, 36, 38, 40, 43–47, 49], and retear can lead to the deterioration of the clinical outcome. The retear rate depends on the size of the rotator cuff tear [2, 4, 5, 8, 10, 11, 14, 21, 29, 33, 35, 37, 38, 41, 42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicting a retear before surgery may help surgeons and patients select the optimal treatment. Regarding the retear rate, many previous studies have reported retear rates ranging from 5 to 57% [1, 6, 7, 9, 12, 13, 16, 20, 22–24, 26, 31, 32, 34, 36, 38, 40, 43–47, 49], and retear can lead to the deterioration of the clinical outcome. The retear rate depends on the size of the rotator cuff tear [2, 4, 5, 8, 10, 11, 14, 21, 29, 33, 35, 37, 38, 41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…The retear of a repaired tendon is one of the most severe complications after arthroscopic rotator cuff repair (ARCR). The rate of retear has been reported to be 5–57% [1, 6, 7, 9, 12, 13, 16, 20, 22–24, 26, 31, 32, 34, 36, 38, 40, 43–47, 49], and some previous studies reported that the postoperative clinical outcomes in patients with retears after ARCR were significantly inferior to those in patients who healed [3, 34, 47].…”
Section: Introductionmentioning
confidence: 99%